The Use of Diorama Learning Media Towards Learning Motivation of Students in Class X IPS 2 - Fitri, Imelda Setya; Zulfan, Zulfan; Rosita, Dara (Riwayat: Educational Journal of History and Humanities, 2022)
The research entitled The Use of Diorama Learning Media on Student Motivation in Class X Social Sciences 2 SMA Negeri 1 Rundeng District". This study aims to determine the effect of using diorama learning media on students' motivation to learn history at SMA Negeri 1 Rundeng District. This study uses a qualitative approach while the type of research is descriptive. The subjects in this study were all students of class X IPS 2 SMA Negeri 1 Rundeng District, totaling 17 students. Sampling technique using purposive sample or sample purpose. selecting this sample was based on the teacher's reference which allowed the data collection techniques to be used were observation, interviews and documentation.Meanwhile, the data analysis technique in this study begins with data reduction, then data model (data display), and ends with verification (conclusion) Based on the data analysis carried out, the average level of motivation obtained by students in class X IPS 2 SMA Negeri 1 R undeng District is highly motivated. Based on the calculation of the percentage scores obtained by students in class X IPS 2 consisting of 82%, 90%, 94%, 96%, 98%, 100% and if added as a whole, the average percentage score is 88%, the results fall into the category very motivated. It can be concluded that there is an effect of using diorama learning media on the motivation to learn the history of students in class X IPS 2 SMA Negeri 1 Rundeng District.